Higher education marketing a critical discourse analysis of the texts found in the "About Us" pages of AMA University and STI Colleges websites - Ilagan, Kristina Cassandra A. (College of Arts and Letters, University of the Philippines Diliman, 2013)
This study aims to understand how AMA University and STI Colleges use language on their websites to represent themselves in relation to their potential students. To do this, linguistic strategies are examined. The meanings behind these linguistic strategies are interpreted based on the researcher's knowledge and background assumptions. These background assumptions constitute the researcher's member's resources (MR) which leads into thinking that higher institutions are now behaving like corporate enterprises competing with their rivals to sell products to customers. Such behavior influences their language choices, thereby affecting how they represent themselves to students. This study analyzes the texts of "About Us" Pages found in AMA University and STI College websites. Studies concerning websites are points of interest since they are new channels in which schools can promote their efforts and establish their identities. Moreover, the increase of website usage in college-selection process among students proves that website-related studies are relevant in contemporary culture. The study reveals that both schools adopt a language that would help them build a positive image. Likewise, they use repeated textual structures to emphasize achievements and thereby accentuate their position over competitors. Apart from this, they also build relations with their viewers. This is by projecting a friendly tone and establishing a more personalized relationship with their potential students. It is also proved that these schools build consumers such that they affect their students on how they should think about themselves and about the world at large.